Learning about the genetic risk in my family: Preferences of Italian nurses - Lea Godino; Linda Battistuzzi; Daniela Turchetti; Liliana Varesco; Vanessa Gentili; Paolo Chiari; Alvisa Palese (Journal of Community Genetics, 2026)
This study explores Italian nurses’ preferences and views regarding the disclosure and sharing of genetic risk information within families, focusing on their genetic literacy and responsibility, and comparing these perspectives with laypeople. A nested cross-sectional online survey, originally designed for the general population, included three hypothetical scenarios of inherited genetic risk (Cystic Fibrosis, Hereditary Cancer Syndromes, and early-onset Alzheimer’s disease) and items assessing genetic literacy (awareness), family cohesion, disclosure preferences, and responsibility. Quantitative data were analyzed descriptively and inferentially, and qualitative responses were analyzed inductively using Reflexive Thematic Analysis. Among the 1,302 respondents, 501 were healthcare professionals (HCPs), including 315 nurses. Their genetic literacy was modest (mean 2.5/4), higher than laypeople’s, with no differences by age or education. Nearly all (94.9%) wished to be informed of genetic risk for at least one condition, with 75.9% preferring to be informed for all three, similar to laypeople (78.1%). Most (97.8%) would undergo genetic testing if informed (95.6% of laypeople). Responsibility for disclosure was viewed as shared between relatives and HCPs (39.1%) or by everyone involved (themselves, relatives and HCPs) (25.1%), echoing laypeople’s views. Qualitative findings from the few who did not wish to be informed ( n = 16) emphasized anxiety, psychological self-protection, and scepticism toward predictive medicine, similar to laypeople. Italian nurses expressed views and preferences similar to laypeople. While they valued receiving genetic risk information and HCP involvement in family communication, limited familiarity with clinical applications of genetic testing highlights a gap in nursing education and practice, with implications for targeted training.

Cascade testing as the missing link in cancer prevention among Lynch syndrome families - Lea Godino; Giulia Erini; Giovanni Innella; Sara Miccoli; Simona Ferrari; Pamela Magini; Luca Caramanna; Martina Preite; Veronica Simoni; Daniela Turchetti (Familial Cancer, 2026)

“Would you want to know?” Questions of utility and responsibility in Italian laypersons’ preferences about genetic risk communication - Lea Godino; Daniela Turchetti; Linda Battistuzzi; Liliana Varesco; Elena Nardi; Vanessa Gentili; Paolo Chiari; Alvisa Palese (Journal of Community Genetics, 2025)
We surveyed the preferences of Italian laypersons ( n = 609) regarding the communication of genetic risk information to and within families, presenting scenarios about three genetic conditions (Cystic Fibrosis, CF; Hereditary Cancer, HC; and early-onset Alzheimer’s disease, AD). We found that almost all of the participants (565/609, 93%) were interested in receiving genetic risk information about at least one of the diseases, and 95% of these also stated they would have genetic testing. Interestingly, 78% of participants in this subset wanted to be informed of their genetic risk and have testing for all the genetic conditions presented in the survey. The main motivating factors were prevention for HC, reproductive responsibility for CF, and life-planning and emotional preparedness for AD, covering a range of elements of clinical, health-related and personal utility. In addition, over a third of our study participants (198/565, 35.0%) indicated that both family members and healthcare professionals are morally responsible for communicating genetic risk information; over a fourth (148/565 26.2%) felt that the responsibility lies with everyone involved: family members, healthcare professionals and also themselves. Findings indicate that bringing into focus individual needs that go beyond medical care may help improve communication about genetic risk and informed choices about genetic testing. Moreover, the Italian public opinion may be open to the possibility of a proactive role for healthcare professionals in disseminating genetic risk information to family members, particularly within the frame of a collaborative effort.

Developing a questionnaire to explore lay people’s preferences for communicating hereditary conditions within families: insights from a cognitive interview study - Lea Godino; Linda Battistuzzi; Liliana Varesco; Daniela Turchetti; Vanessa Gentili; Paolo Chiari; Alvisa Palese (Journal of Community Genetics, 2025)
Cognitive interviews are a valuable qualitative method for developing and refining survey instruments, particularly on complex topics such as genetic health. They help address misunderstandings between intended meanings and respondent interpretations, enhancing data validity and ensuring comprehensibility. This study aimed to refine a questionnaire exploring the attitudes and preferences of the Italian general population regarding the communication of potential hereditary conditions within families. Through iterative testing, issues related to questionnaire instructions, question wording, and the sensitive nature of the topics were identified and addressed. Most concerns emerged in the first round of cognitive interviews, while the second round only required minor refinements. The qualitative analysis identified four key themes reflecting participants’ challenges in understanding genetic information: (1) difficulties with genetic terminology, including gene names and scientific jargon, which induced anxiety and hindered comprehension; (2) ambiguities surrounding the terms "genetic testing" and "family," with confusion about the nature of genetic testing and the scope of "family" in genetic contexts; (3) misinterpretations of "genetic risk" as an existing disease diagnosis rather than a probabilistic concept, leading to misunderstandings about the implications of genetic predisposition; and (4) conflation of "authorization" and "responsibility" in genetic communication, further complicated by uncertainty regarding privacy and confidentiality. Findings from this study informed targeted modifications to the questionnaire to enhance its clarity and accessibility. Our study highlights the importance of cognitive interviewing in refining survey tools on genetic communication, ensuring that such instruments effectively capture public perceptions and facilitate informed decision-making .

Cascade genetic testing in hereditary cancer: exploring the boundaries of the Italian legal framework - Liliana Varesco; Francesco Di Tano; Juri Monducci; Stefania Sciallero; Daniela Turchetti; Claudia Bighin; Giulia Buzzatti; Irene Giannubilo; Lucia Trevisan; Linda Battistuzzi (Familial Cancer, 2025)

Hereditary breast and ovarian cancer genetic testing in unselected patients: example of private supplementation of public healthcare service - Francesca Fiorentino; Giovanni Innella; Federica Balducci; Laura Marullo; Giulia Lanzoni; Sara Miccoli; Laura Cardarelli; Daniela Turchetti; Sergio Tempesta (Familial Cancer, 2025)

Clinical genetic services in the Emilia-Romagna region, Italy: current activity and open issues: a mixed-method study - Lea Godino; Enrico Ambrosini; Valeria Barili; Claudio Graziano; Livia Garavelli; Olga Calabrese; Marcella Neri; Luca Sangiorgi; Benedetta Bertonazzi; Giovanni Innella; Daniela Turchetti; Antonio Percesepe (Journal of Community Genetics, 2025)
In 2002, in the Emilia-Romagna region of Italy, a comprehensive strategic plan was developed with the aim of improving the integration and efficiency of the genetic services. Two decades later, this report aims to explore the current functioning of the regional network, with special focus on clinical genetics in the evolving scenarios. To this aim, we analyzed the activity data of the medical genetics services in the region, to identify and possibly improve currently open issues. This is a mixed-method study, analyzing quantitatively and qualitatively the activities of seven medical genetics services in Emilia-Romagna region. Quantitative analysis considered the number of consultations and the composition of the staff in the year 2021. Qualitative analysis examined a focus group of directors of the services through reflexive thematic analysis. A total of 14,925 counseling sessions have been delivered by the medical genetics services, staffed with 22.4 full-time equivalent clinical geneticists. A physician performed an average of 14.5 consultations per week and approximately 1166 h of patient care per year. The clinical geneticists/inhabitants ratio was 0.54 per 100,000 inhabitants, and it is estimated that one every 278 inhabitants, on average, underwent a genetic counseling session in 2021. Qualitative analysis highlighted issues concerning patients’ access to service, general organization and staff composition. In order to meet the growing demand for genetic counseling services, expansion of the workforce and adjustment of current practice models are required to increase the access to genetic services and the application of test results to clinical management.

Selective response of soil bacterial and fungal taxa to biodegradable polymers - Alessandro Bernetti; Sofia Barili; Ciro Sannino; Gianmarco Mugnai; Luigimaria Borruso; Irina Pinchuk; Daniela Pezzolla; Benedetta Turchetti; Giovanni Gigliotti; Pietro Buzzini (Environmental Research, 2025)

Cascade testing in Italian Hereditary Breast Ovarian Cancer families: a missed opportunity for cancer prevention? - Lucia Trevisan; Lea Godino; Linda Battistuzzi; Giovanni Innella; Elena Luppi; Giulia Buzzatti; Viviana Gismondi; Eva Blondeaux; Luigina Ada Bonelli; Daniela Turchetti; Liliana Varesco (Familial Cancer, 2024)

Impact of PVC microplastics on soil chemical and microbiological parameters - Sofia Barili; Alessandro Bernetti; Ciro Sannino; Nicolò Montegiove; Eleonora Calzoni; Alessio Cesaretti; Irina Pinchuk; Daniela Pezzolla; Benedetta Turchetti; Pietro Buzzini; Carla Emiliani; Giovanni Gigliotti (Environmental Research, 2023)

Genetic counselling as a route to enhanced autonomy: using a sequential mixed methods research approach to develop a theory regarding presymptomatic genetic testing for young adults at risk of inherited cancer syndromes - Lea Godino; Daniela Turchetti; Leigh Jackson; Catherine Hennessy; Heather Skirton (Journal of Community Genetics, 2021)

Implementing genetic education in primary care: the Gen-Equip programme - Milena Paneque; Martina C Cornel; Vaclava Curtisova; Elisa Houwink; Leigh Jackson; Alastair Kent; Peter Lunt; Milan Macek; Vigdis Stefansdottir; Daniela Turchetti; Heather Skirton (Journal of Community Genetics, 2017)

Description of Taphrina antarctica f.a. sp. nov., a new anamorphic ascomycetous yeast species associated with Antarctic endolithic microbial communities and transfer of four Lalaria species in the genus Taphrina - Laura Selbmann; Benedetta Turchetti; Andrey Yurkov; Clarissa Cecchini; Laura Zucconi; Daniela Isola; Pietro Buzzini; Silvano Onofri (Extremophiles, 2014)

Changes in breast cancer incidence and stage distribution in Modena, Italy: the effect of a mammographic screening program - Daniela Turchetti; Lucia Mangone; Rossella Negri; Giulio Rossi; Laura Cortesi; Marco Vinceti; Antonino Maiorana; Ennio Gallo; Massimo Federico (Cancer Causes & Control, 2002)